The Relationship Between Jonathan and David From the Perspective of the Vulgate - Fieger, Michael (Vulgata in dialogue, 2025)
In the Vulgate, the famous friendship of Jonathan and David is described in the Vulgate with the verb diligere and the noun amor . While we do not know anything about the translator’s – Jerome’s – attitude toward homosexuality, he did not hesitate to use words that may imply a homoerotic relationship.